Preparing midwifery students for traumatic workplace events: Findings from the POPPY (programme for the prevention of posttraumatic stress disorder in midwifery) feasibility study. (December 2018) - Spiby, Helen; Sheen, Kayleigh; Collinge, Sarah; Maxwell, Clare; Pollard, Kerry; Slade, Pauline
Abstract: Background: Midwifery students can experience events on clinical placements that they perceive to be traumatic. There is currently no requirement to provide training about the nature of trauma, normal responses, or the most helpful ways of self-managing these. The POPPY programme, developed for qualified midwives, incorporates educational (the POPPY workshop) and supportive resources to prevent the development of Post-Traumatic Stress Disorder in midwives. As part of the feasibility evaluation of POPPY, the POPPY workshop element was adapted for pre-registration midwifery students (PreR-POPPY). Attention to this issue during pre-registration education could improve student experience and support student retention. Objectives: To identify students' perspectives on the contents (clarity, understandability, organisation of the workshop, utility, relevance), their understanding of trauma and psychological responses, and confidence in recognising and managing early signs of distress following participation in a PreR-POPPY workshop. Perspectives on preferred timing in their midwifery programmes, and methods of delivery were also sought. Design: In keeping with educational evaluations, anonymous feedback was collected from students. Setting: Two higher education institutes. Participants: Midwifery undergraduate students on the three year or shortened programme for registered nurses (n = 131), and midwifery educators (n = 5). Methods: Students participated in the workshop and provided feedback immediately. Midwifery educators participated in a meeting with the researchers to provide feedback. Results: High levels of satisfaction with the contents of the workshop were identified. Ninety-nine percent of students would recommend the workshop to other midwifery students. Provision of the workshop early in midwifery programmes, revisited at later points, was strongly endorsed. Learning outcomes were very positive for understanding trauma/early stress responses, and recognising and managing early responses to trauma. Strong endorsement for the provision of the workshop was received from the midwifery educators. Conclusions: The pre-registration adapted POPPY workshop should be routinely provided in preregistration midwifery.